Diplomacia Naval: um balanço da literatura clássica - Waldmann Júnior, Ludolf (2024)
Historically, navies have been employed used both for waging wars and in non-combat roles, with a notable emphasis on their use in promoting or pursuing foreign policy objectives during times of peace. This perspective is the focus of naval diplomacy, developed by naval historians and analysts in the 1960s and 1970s, which continues to capture the attention of scholars despite changes in approaches, theoretical perspectives, and the international context. The aim of this article is to provide an overview of classic authors in naval diplomacy, showcasing their concepts and primary contributions.